EFL Students’ Reflection on Media Use in English Class - Salmin Ahmad; Suhartini Syukri; Nurhasanah Safei (AL LUGHAWIYAAT, 2020)
This qualitative study aims to investigate the use of media in English class based on the students’ reflection at one of vocational schools in Kendari. Three kinds of instruments used in study are observation sheet, journal reflection, and documentation sheet gathered from 34 students. The result of the study reveals that the students respond positively to the use of teaching media in English class. The students also find out the use of teaching media in English class is beneficial to them. One of the benefits is it can help improve students understanding of the material delivered by the English teacher in the classroom. This implies that the use of media in the English class should be encouraged in order to improve the students’ motivation in learning English and the students can understand the material easily when the teacher explains the material in the classroom.Keywords: Media use; reflection journal.